SISTEM PAKAR UNTUK DIAGNOSIS PENYAKIT AYAM YANG DISEBABKAN OLEH VIRUS - Bambang Yuwono (Jurusan Teknik Informatika, 2010)
This research based on necessery of a tool which can help for breeder or extension agent in diagnosing disease of chicken livestock which is because of virus. The tool is an expert system which is besides to diagnose, this system is expected able to give the medication suggestion. This Expert system to communicate with the user in the form of question